Emergency forced pandemic e-learning – feedback from students for HEI management. (2nd September 2021) - Kulikowski, Konrad; Przytula, Sylwia; Sulkowski, Lukasz
ABSTRACT: The COVID-19 pandemic created many challenges for higher education institutions (HEI), one of the most important being forced e-learning – the involuntary need to move all educational activities to an online environment. In this exploratory study, we aim to learn from students' feedback on demands created by COVID-19 forced e-learning to provide HEI management with insights helpful in building educational policies that might promote students' positive perception of distance learning in turbulent times. Based on a convenience sample of more than 600 university students we implemented multiple regression analysis to explore the relationships between e-learning demands experienced by students and the three dimensions of e-learning perception: emotional experience with e-learning, cognitive evaluation of e-learning, and study engagement in e-learning. Our findings have shown that the e-learning demand most strongly related to a negative perception of e-learning was students' belief that during e-learning the university was plunged into chaos. This suggests that for students who participate in e-learning, the most important aspect of e-learning policy might be not, as we often intuitively think, the cutting edge e-learning platform & technology but rather effective reciprocal communication between HEI and students about the e-learning situation, allowing a perception of order to be created.